A changing marine sector in Australian coastal communities: An analysis of inter and intra sectoral industry connections and employment. (November 2016) - van Putten, Ingrid; Cvitanovic, Christopher; Fulton, Elizabeth A.
Abstract: The human population is concentrated in coastal regions around the world, and while much of this is in large urban centres, recent years have seen significant growth among smaller regional coastal centres. The economic sectors of these smaller coastal communities have historically been driven by marine based economic activities like fishing. However, there has been a decline in the fishing sector and in some communities other marine related activities – such as aquaculture, tourism, off shore oil and gas, ports, and transport (collectively called the marine sector) – are growing instead. The industry makeup of the marine sector is changing, which presents challenges to some coastal communities forced to reshape their economic activities and diversify across the portfolio of marine industries. Doing so requires intricately linked networks of businesses and services, potentially across industries, that each rely on a flow of inputs from their suppliers and downstream industries to take their product. Using Australia as a case-study, this study uses national level Input-Output (IO) data to quantify industry connections to different marine industries and assess those that may be crucial for the continued existence or future growth of the marine sector. Results show that while fishing and aquaculture are reliant on several overlapping up- and downstream industries, and some synergies exist with marine tourism, there is little overlap with other marine industries. Although marine tourism is the largest employer in small regional coastal communities across all states, employment in fishing and aquaculture is more important in small regional coastal communities than in any other type of community. These communities are most at risk of not being able to build or maintain intricate industry connections necessary for diversifying into new marine industries. The differences in the structure of the marine sector among coastal communities according to their location and size suggests that a decline in traditional marine industries will have a disproportional effect on the economic security and thus social well-being of certain communities, and highlights the need for targeted and location specific governance and policy responses to build resilience among the marine sector in coastal communities. Highlights: Geographic differences in the structure and composition of employment in the marine sector. Marine tourism is the largest employer in small regional coastal communities across all states. Few overlaps in industry connections between other marine industries and fishing and tourism. Fishing and aquaculture larger role in small coastal communities where employment is most at risk. Multi-level policy responses required to improve economic viability of coastal communities.